(x – 2) ³ – (x – 3)(x ² + 3x + 9) + 6(x + 1) ² = 15

(x – 2) ³ – (x – 3)(x ² + 3x + 9) + 6(x + 1) ² = 15

2 bình luận về “(x – 2) ³ – (x – 3)(x ² + 3x + 9) + 6(x + 1) ² = 15”

  1. (x-2)^3-(x-3)(x^2+3x+9)+6(x+1)^2=15
    =>x^3-6x^2+12x-8-(x^3-27)+6(x^2+2x+1)=15
    =>x^3-6x^2+12x-8-x^3+27+6x^2+12x+6=15
    =>(x^3-x^3)+(6x^2-6x^2)+(12x+12x)+(27+6-8)=15
    =>24x+25=15=>24x=-10
    =>x=-5/12

    Trả lời
  2. Giải đáp : x = -5/12
    Lời giải và giải thích chi tiết:
    ( x – 2 )^3 – ( x – 3 )( x^2 + 3x + 9 ) + 6( x + 1 )^2 = 15
    <=> x^3 – 6x^2 + 12x – 8 – x^3 + 27 + 6( x^2 + 2x + 1 ) = 15
    <=> -6x^2 + 12x + 19 + 6x^2 + 12x + 6 = 15
    <=> 24x = -10
    <=> x = -5/12
    Vậy x = -5/12

    Trả lời

Viết một bình luận

Câu hỏi mới